Regional Fiscal Dynamics: The Influence of Local Revenue and Transfer Receipts on Capital Expenditure - Rineliana, Rineliana; Susanto, Edi; Gunawan, Agung; Tampubolon, Omar Farrakhan; Tampubolon, Dahlan (Jurnal Ilmu Manajemen Advantage, 2025)
This study aims to comprehensively analyze the influence of various regional income types (PAD, DAU, DBH, and Non-Physical DAK) on capital expenditure allocation across districts/cities in Riau Province. This study uses secondary data, including DAU, PAD, Non-Physical DAK, DBH, and Capital Expenditure, from BPKAD and the Directorate General of Treasury of Riau Province. Data collection uses documentation from the websites of the Directorate General of Fiscal Balance, BPKAD, and the Directorate General of Treasury of Riau Province. The development of various types of income across districts/cities in Riau Province showed a positive trend during the study period, with DBH making a significant contribution, reflecting the region's rich natural resources. The trend and growth of capital expenditure in district/city governments in Riau Province fluctuated but generally increased. However, its proportion to total regional spending is still relatively low. DBH has the most significant influence on capital expenditure in districts/cities in Riau Province, followed by DAU, PAD, and Non-Physical DAK (not significant). The high impact of DBH and DAU on capital expenditure indicates a high fiscal dependence of regional governments on central government transfers for financing infrastructure development.